Diabetes mellitus screening and its associated factors among women in Lesotho: evidence from the 2023–2024 demographic and health survey - Enyew Getaneh Mekonen; Deresse Abebe Gebrehana; Tadesse Tarik Tamir; Alebachew Ferede Zegeye; Berhan Tekeba (BMC Endocrine Disorders)
Abstract Background Diabetes screening is one of the simpler methods for preventing and lowering the disease’s morbidity and mortality. Screening for gestational diabetes is a crucial component of obstetric care, as it negatively affects the life of both the mother and the fetus. There is a high prevalence of obesity, diabetes, high blood pressure, and tobacco use in Lesotho. This highlights the significance of bolstering prevention and treatment initiatives in the country. Therefore, this study is intended to assess diabetes screening and its associated factors among women aged 15–49 years using the 2023-24 Lesotho demographic and health survey dataset. Methods A cross-sectional study was employed using data from the most recent national representative dataset. A total sample of 3,297 women aged between 15 and 49 years was included in the study. Data extracted from the Lesotho Demographic and Health Survey 2023-24 data sets were cleaned, recoded, and analyzed using STATA/SE version 14.0 statistical software. Multilevel logistic regression was used to determine the factors associated with the outcome variable. Finally, variables with a p-value less than 0.05 were declared statistically significant. Results In the current study, 29.18% (95% CI: 27.65%-30.75%) of women aged 15–49 years in Lesotho were screened for diabetes mellitus. Of these, 1.40% of them had high blood sugar or diabetes, and 54.35% of women were diagnosed in the last twelve months. Age of respondents [AOR = 3.53; 95% CI (2.80, 4.46)], maternal occupation [AOR = 1.38; 95% CI (1.15, 1.65)], wealth status [AOR = 1.43; 95% CI (1.07, 1.91)], and visiting a healthcare facility in the last 12 months [AOR = 1.31; 95% CI (1.09, 1.57)] were statistically significantly associated with diabetes screening. Conclusion Less than one in three women aged 15 to 49 years were screened for diabetes in Lesotho. Advanced age, working women, wealthier households, and visiting a healthcare facility in the last 12 months were associated with higher odds of diabetes screening. Therefore, women’s empowerment, regular visits to healthcare facilities, and awareness creation for young women are recommended to improve diabetes screening practices among women.